IDENTIFICATION OF CRUSTAL BLOCKS BASED ON GPS DATA - Mukhamediev Sh.A.; Zubovich A.V.; Kuzikov S.I. (My University, 2006)
The style of the continental crust deformation is nowadays the most discussed topic of geodynamics. According to one concept, the lithosphere is an assemblage of microplates (blocks) and its deformation is caused by displacements along the block boundaries. According to an alternative concept, the lithosphere deformation is distributed throughout the volume and corresponds to a rheological model of nonlinear viscous fluid.